Antecedents and adaptations in the borderlands: a social history of informal socio-economic activities across the Rhodesia-Mozambique border with particular reference to the city of Umtali, 1900-1974 - Duri, Fidelis Peter Thomas (My University, 2012)
This work explores the informal pursuits for a livelihood across the border separating the Rhodesian town of Umtali and the Portuguese colony of Mozambique by Africans marginalised by colonial rule during the period 1900-1974. Some of these activities pre-dated the advent of European colonisation while others were improvised during the colonial period. This study focuses on five forms of informal cross-border activities, namely: socio-cultural interactions, irregular labour mobility and practices, the theft of property in Umtali and its disposal in Mozambique, illicit alcohol brewing and commerce, and dagga trafficking. Without overlooking the role of other social networks based on gender, class and generation, it is the central contention of this thesis that family and kinship affiliations and dynamics dating back to the pre-colonial period and those that prevailed, and at times forged after the advent of colonisation, played a significant role in the development of informal cross-border pursuits for a livelihood by marginalised Africans. These activities in turn, together with other prevailing socio-economic dynamics, sometimes enhanced or destabilised family and kinship solidarity. Without necessarily deconstructing other analytical tools such as gender, class and generation, this thesis seeks to underline the importance of family and kinship dynamics as a tool of analysis in the study of informal cross-border activities.
Ph.D. University of the Witwatersrand, Faculty of Humanities, 2012